Organizational communication and its role as a major requirement for improving knowledge sharing among faculty members in emerging Saudi universities (survey study) | الاتصال التنظيمي ودوره بوصفه متطلبا رئيسا لتحسين مشاركة المعرفين بين أعضاء هيئة التدريس بالجامعات السعودية الناشئة (دراسة مسحية) - Al Qahtani | القحطاني , Abd Allah Ben Ali | عبد الله بن علي (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
The current study aimed to identify the role of organizational communication, as one of the main requirements for improving knowledge sharing among faculty members in Saudi universities. The importance of this study stems from the fact that it addresses a contemporary issue that represents a problem that has become prevalent in contemporary universities, especially emerging ones. Despite the application of organizational communication in emerging universities, there are still many obstacles that prevent Translate those communications into effective knowledge management practices. The study sample included 120 faculty members in emerging Saudi universities, and the researcher used the descriptive approach, using the survey method as a study method, relying on the questionnaire that he prepared to achieve the objectives of the study. | هدفت الدراسة الحالية إلى التعرف على دور الاتصال التنظيمي، بصفته أحد المتطلبات الرئيسة لتحسين مشاركة المعرفة بين أعضاء هيئة التدريس بالجامعات السعودية. وتنبع أهمية هذه الدراسة من أنها تتناول قضية معاصرة تمثل مشكلة أصبحت سائدة في الجامعات المعاصرة، ولا سيما الناشئة منها، فعلى الرغم من تطبيق الاتصال التنظيمي في الجامعات الناشئة، لا تزال هناك العديد من المعوقات التي تحول دون ترجمة تلك الاتصالات إلى ممارسات فعالة لإدارة المعرفة. واشتملت عينة الدراسة على 120 عضو هيئة تدريس بالجامعات السعودية الناشئة، واستخدم الباحث المنهج الوصفي، وذلك باستخدام الأسلوب المسحي منهج اللدراسة، معتمدا على الاستبانة التي قام بإعدادها لتحقيق أهداف الدراسة